ANALISIS PENGELOLAAN MODAL KERJA DAN SIKLUS OPERASI TERHADAP LIKUIDITAS PERUSAHAAN - Soemantri, Samuel; Supriadi, Yoyon; Renda, Citra Sari (LPPM Institut Bisnis dan Informatika Kesatuan, 2015)
With the development of today's business world, the competition among companies, especially among similar companies will be more stringent. To maintain the viability, companies are facing tight competition, thus necessary resource management will be undertaken by the management, in addition to the demand to be able to coordinate the use of all resources owned by the company eficiently and affectively The purpose of this research is to determine how the management of working capital, operating cycle, and enterprise liquidity, and also to determine how much influence the management of working capital and operating cycle have on the company's liquidity. Research is done on two similar companies, namely PT Mandom Indonesia Tbk and PT Mustika Ratu Tbk period from 2007 through 2013 data used are secondary data. There are three variables in this study, namely working capital, operating cycle, as an independent and liquidity as a dependent. The method used is the ratio analysis method, namely the working capital turnover, the operating cycle and the current ratio. The hypothesis of this study is the management of working capital and operating cycles have significant positive relation on the company's liquidity. The results of this study prove that the partial management of working capital and operating cycle has a positive relation but not significant on the liquidity and simultaneously, working capital management and operating cycle have positive but not significant effect . Keywords: working capital, operating cycle, liquidity